Impact of Climate Changes on Cotton Crop in Punjab - Wajahat Majeed Khan; Muhammad Yousaf Khan (Dialogue Social Science Review (DSSR), 2025)
A major issue impacting agricultural output worldwide, especially in emerging nations like Pakistan, is climate change. The country's main cotton-producing area, Punjab, is dealing with severe temperature swings, unpredictable rainfall patterns, and a rise in the frequency of extreme weather events. With an emphasis on changes in temperature, precipitation, and other climatic variables during the previous 20 years, this study investigates the regional effects of climate change on Punjab's cotton crop productivity. The study uses a combination of qualitative and quantitative techniques, such as analyzing agricultural yield figures, weather data, and local farmer interviews. The results of research study show a significant drop in cotton output, which is directly related to warming temperatures, water scarcity brought on by erratic monsoon rains, and the spread of pests made worse by shifting weather patterns. Additionally, the implications of Punjab's geographical variance vary, with the southern parts being more vulnerable because of their arid environment and scarce irrigation supplies. In order to lessen the negative impacts of climate change on Punjab's cotton output, this article emphasizes the urgent need for climate-resilient crop types, adaptive agricultural techniques, and better irrigation management.